Dimethyl sulfoxide (DMSO) exposure to human peripheral blood mononuclear cells (PBMCs) abolish T cell responses only in high concentrations and following coincubation for more than two hours. - Kloverpris, H; Fomsgaard, A; Handley, A; Ackland, J; Sullivan, M; Goulder, P (2010)
Immunotherapies based on reinfusion of autologous cells incubated ex vivo with peptides reconstituted in toxic solvents, such as DMSO, are now performed on a routine basis. However, the toxic effects of the most common solvent used, DMSO, on T cell responses from human PBMCs, have not previously been evaluated in detail. Here, in preparation for a first-in-man human phase I vaccine trial comprising reinfusion of autologous HIV peptide-pulsed PBMCs, human PBMCs from healthy and HIV-infected donors were exposed in vitro to a range of DMSO concentrations, and for a range of time periods. Polychromatic flow cytometry was used to evaluate the influence of DMSO on functional T cell responses. We report that high concentrations of up to 10% of DMSO for 1 hour do not affect the cell viability, the magnitude or the functional profile of CD4(+) and CD8(+) T cell responses, regardless of antigen specificity and HLA class I restriction. In contrast, >2% for >2 hours compromises these responses. These data are relevant in the design of immunotherapies based on pulsing a large number of peptides onto antigen presenting cells prior to reinfusion.